The antecedents of sustainable shipping management and organisational performance: resource accumulation and orientation perspectives - Tran, Thi Minh Trang (2022)
Purpose: Sustainable shipping management (SSM) has received much attention from shipping companies in recent years. Grounded on resource accumulation and orientation perspectives, this study aims to identify the antecedents of SSM and examine their effects on the performance (i.e. shippers' loyalty and financial performance) of shipping companies. Design/methodology/approach: A model comprising a network of hypotheses that specifies the relationships between the antecedents, SSM, shippers' loyalty and financial performance was constructed. Subsequently, a survey questionnaire was designed. Survey data were then collected from 294 shipping companies located in Vietnam and analysed using structural equation modelling. Findings: The findings indicate that the five antecedents have significant effects on the effectiveness of SSM. They are stakeholders' focus, strategic orientation, supply chain collaboration, sustainability resource development and sustainability technology development. Bootstrapping analysis indicates that SSM has significant direct and indirect effects on financial performance via shippers' loyalty. Research limitations/implications: Applied perspectives are complementary and offer unique explanations to SSM. However, the orientation perspective offers stronger explanation. This study also improves the allocation of resources and capabilities in managing sustainability to enhance the organisational performance of shipping companies. Originality/value: This study synthesises the sustainability and strategic management literature to identify the antecedents of SSM.